Desain dan Analisis Performa Mesin Pemipil Jagung Portabel Berkapasitas Sedang - Haikal; Arif Hidayat Purwono; Agus Jamaldi; Bambang Margono; Edy Suryono; Johanes Wawan Joharwan; Apri Wiyono; Isnarno Isnarno; Dewi Ratna Nurhayati (Politeknik Negeri Lampung., 2023)
Corn shelling tools have developed in Indonesia ranging from very simple corn shellers to mechanical corn shellers. However, the maize sheller with a medium-scale capacity has not been well developed. The research objective was to design and analyze the performance of a medium-capacity portable corn sheller machine to meet the maize harvest processing process, which can increase productivity, the quality of maize shelled with medium-scale capacity and also develop a new shelling tool design. This research was conducted in 3 stages, namely field observation, design, and machine performance. The results showed a corn sheller machine with a 0.5 hp electric motor. The results of the work show that the speed of the shelling process is very influential on the results of the shelling. The higher the speed of the shelling process, which is 2400 rpm, the better or no leftover corn is shredded.